(untitled) (The Shivapuri Journal, 2025)
One of the oldest military strategy books in the world, Sun Tzu’s Art of War is a well known classic from the warring states era that has been in print for more than 2,500 years. It is still studied and used extensively in military strategy, politics, entrepreneurship, and investing among other areas. The article’s goal was to assess Art of War’s relevancy in modern warfare. The study examined the tenets of Art of War, its application in the 20th century, and its applicability in the present. Discussed three wars of the twenty-first century-the war in Afghanistan from 2001 to 2021, the war in Iraq from 2003 to 2011, and the current war between Russia and Ukraine. They concluded that the Art of War is still relevant today, just as it was twenty-five centuries ago, because whenever political and military leaders followed the Art of War, they have won, and whenever they disregarded the key works of the Art of War, they have lost. This study employs qualitative analysis of secondary data, including historical records, military reports, and scholarly articles.